Cranial Meningiomas Requiring Cranioplasty. (15th October 2021) - Norrington, Max; Millward, Christopher; Doherty, John; Mustafa, Mohammad; Humphries, Thomas; Gillespie, Conor; Richardson, George; Islim, Abdurrahman; Jenkinson, Michael; Brodbelt, Andrew
Abstract: Aims: Bone infiltration in association with intracranial meningioma (4.5% of cases) and primary intraosseous meningioma (2%) are rare. Management can be challenging, as cranial vault reconstruction may be required. This study aimed to examine the surgical techniques used and outcomes in this patient population. Method: A single-centre, retrospective cohort study was conducted between January 2010 and September 2020. All adult patients who required cranial reconstruction due to bone involvement of their meningioma were included. Patient demographics, tumour characteristics, operative details, complications, and outcomes were examined. Statistical analyses were performed using SPSS v24.0. Results: There were 30 patients (17 female; 56.7%), median age 54 yrs (range 28-86 yrs), of whom 25 (83.3%) had bone infiltration, and 5 (16.7%) had primary intraosseous meningioma. Only 10 patients had a Simpson I or II resection. Twenty-eight had 'on-table' primary cranioplasties. Materials used were titanium (n=13; 43.3%), acrylic (n=10; 33.3%), PMMA (n=5; 16.7%), and hydroxyapatite (n=2; 6.7%). There were 9 (mostly minor) surgical complications and only one wound infection. Twelve patients had WHO grade II tumours, and 14 required radiotherapy. Ten patients (33.3%) had re-operation for recurrent tumour, with a median time to progression of 41 months. At 6 months, 24 patients had a performance score less than 2. Conclusion: On-table cranioplasty provides a lower risk surgical option for patients with high risk meningiomas.